2020
DOI: 10.1177/2150132720958532
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Gender-Based Difference in Adherence to Influenza Vaccination during the 2018-2019 Season

Abstract: Introduction: Improving flu vaccination rates in the general population is an important and effective strategy toward reducing morbidity, mortality, and the cost of seasonal influenza. In order to optimize immunization strategies, factors associated with decreased vaccination rates need to be explored. The literature suggests that there is a gender difference in the rate of influenza vaccination but is limited to population-based survey studies and also is inconsistent as to which gender has a higher rate of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 13 publications
(25 reference statements)
2
28
2
Order By: Relevance
“…Similarly, a May 2020 study by Malik and colleagues found that males (72%) were more likely to accept COVID-19 vaccine than females (63%) [ 7 , 15 17 , 23 ]. In general, women are more likely to practice preventive behaviors and avoid risk behaviors (e.g., influenza vaccination rates in the US and wearing of face masks to prevent COVID-19 infections) [ 24 26 ]. However, the results of COVID-19 vaccine hesitancy have been mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a May 2020 study by Malik and colleagues found that males (72%) were more likely to accept COVID-19 vaccine than females (63%) [ 7 , 15 17 , 23 ]. In general, women are more likely to practice preventive behaviors and avoid risk behaviors (e.g., influenza vaccination rates in the US and wearing of face masks to prevent COVID-19 infections) [ 24 26 ]. However, the results of COVID-19 vaccine hesitancy have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed on sex, parenthood, and family structure for COVID-19 vaccine hesitancy in light of influential factors such as risk perception, access to healthcare and health literacy, attitudes and beliefs, differential COVID-19 vulnerability and comorbidity burden based on sex, pre-existing vaccine hesitancy, safety and efficacy concerns, the effect of conspiracy theories associated with vaccines (e.g., for children and autism risk, deleterious effects of a vaccine potentially compromising the ability to care for children. unknown long-term sequelae, the seriousness of the infection due to vaccine), just to name a few [ 7 , 15 17 , 23 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In literature, females usually tended to have higher prevalence of health-related service utilization (e.g., mental health services) [ 36 , 37 ]. However, they showed stronger vaccine hesitancy (including influenza vaccination and COVID-19 vaccination) than males [ 17 , 21 ], although mixed findings have been reported [ 6 , 38 ]. This study may be the first to explore why females tended to have lower COVID-19 vaccination rates than males.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been shown in other health-related surveys in Germany [ 26 ] and Europe [ 27 ] and seems to be a general phenomenon [ 28 ]. This might be explained by a higher health awareness that is also reflected by the higher influenza vaccination rates in women [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We think it is possible that this interaction is overlooked in studies that do not cover such a broad age spectrum as in the PROCLAIR surveys. A possible reason for younger women participating more often than younger men might be higher health awareness among the women, while elderly men and women seem to have equal health behavior [ 29 ].…”
Section: Discussionmentioning
confidence: 99%